2022
DOI: 10.1038/s41598-022-10108-z
|View full text |Cite
|
Sign up to set email alerts
|

Impact of weather parameters on Alternaria leaf spot of soybean incited by Alternaria alternata

Abstract: Weather attributes play a crucial role in the infection process and spread of pathogen. Alternaria leaf spot incited by Alternaria alternata is most destructive disease of soybean appeared in southern and eastern parts of Rajasthan as well as India. The effect of various weather parameters along with different date of sowing on the development of Alternaria leaf spot in susceptible soybean cultivar RKS-24 was investigated during Kharif season 2018 and 2019. The various weather factors viz., temperature, relati… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
11
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 22 publications
(16 citation statements)
references
References 12 publications
0
11
0
Order By: Relevance
“…The seed yield per hectare was higher in October and November plantings than in December. According to Fagodiya et al (2022), the severity of Alternaria leaf spot in soybean crops, as measured by the variance of AUDPC, is influenced by both the month of sowing and weather conditions. They found that various weather parameters and sowing dates play a significant role in the onset of the disease, affecting the infection process and pathogen spread.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…The seed yield per hectare was higher in October and November plantings than in December. According to Fagodiya et al (2022), the severity of Alternaria leaf spot in soybean crops, as measured by the variance of AUDPC, is influenced by both the month of sowing and weather conditions. They found that various weather parameters and sowing dates play a significant role in the onset of the disease, affecting the infection process and pathogen spread.…”
Section: Resultsmentioning
confidence: 99%
“…In the cluster bean leaf blight, Sharma et al (2020) found the same kind of correlation matrix. Early studies on the various diseases caused by Alternaria also revealed a negative correlation between temperatures (maximum and minimum) and disease severity, while a positive correlation existed between relative humidity and rainfall (Bajaya et al, 2022;Fagodiya et al, 2022). It might be due to the favourable temperature for spore germination of Alternaria is the temperature in the range of 18°C and 24 °C and relative humidity levels above 90% (Nowicki et al, 2012).…”
Section: Environment Conservation Journalmentioning
confidence: 99%
“…We can distinguish several factors affecting the occurrence of soybean diseases [11][12][13][14][15][16][17]. The most important factors influencing the severity of plant diseases in European conditions are variable temperature and rainfall conditions.…”
Section: Introductionmentioning
confidence: 99%
“…Weather conditions can have a positive or negative impact on plant development. Frequent rainfall and high moisture levels are conducive to the development of diseases [11]. Cultivation practices influencing the intensity of fungal diseases include crop sequences and the regionalization of cultivars [17,18].…”
Section: Introductionmentioning
confidence: 99%
“…It is likely that elevated CO 2 and higher temperatures will increase fungi invasions and toxin production, although the response will be dependent on the host/pathogen combination [ 26 , 27 , 28 ]. In particular, future climatic conditions are expected to change Alternaria incidence and toxin production [ 15 , 29 , 30 , 31 ], because elevated CO 2 alters phytohormone and reactive oxygen signaling, secondary metabolism, and defense-associated development such as stomatal responses in the host [ 32 ], resulting in a higher vulnerability of hosts to phytopathogens such as Alternaria . Possible strategies to limit Alternaria infection include: (1) obtaining resistant cultivars in breeding programs.…”
Section: Introductionmentioning
confidence: 99%